2017
DOI: 10.1093/mnras/stx1458
|View full text |Cite
|
Sign up to set email alerts
|

NGC 1566: analysis of the nuclear region from optical and near-infrared Integral Field Unit spectroscopy

Abstract: We analysed the centre of NGC 1566, which hosts a well-studied active galactic nucleus (AGN), known for its variability. With the aid of techniques such as Principal Component Analysis Tomography, analysis of the emission-line spectra, channel maps, Penalized Pixel Fitting and spectral synthesis applied to the optical and near-infrared data cubes, besides the analysis of Hubble Space Telescope images, we found that: (1) the AGN has a Seyfert 1 emission, with a very strong featureless continuum that we describe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 52 publications
4
25
1
Order By: Relevance
“…The narrow Fe Kα line intensity can change by a factor of 1.5 for the corresponding continuum variation within a time interval as short as four months. This allows us to put the material responsible for producing the narrow Fe Kα line at a distance scale to <0.1pc, comparable to the size of BLR which is ∼ 0.01pc inferred for NGC 1566 (Alloin et al 1985;da Silva et al 2017). The rapidly variable narrow Fe Kα line have also been reported in the AGN NGC 4151 (Zoghbi et al 2019), which can be explained as originating from the inner BLR.…”
Section: Response Of the Fe Kα Emission To The Longterm X-ray Continu...supporting
confidence: 60%
“…The narrow Fe Kα line intensity can change by a factor of 1.5 for the corresponding continuum variation within a time interval as short as four months. This allows us to put the material responsible for producing the narrow Fe Kα line at a distance scale to <0.1pc, comparable to the size of BLR which is ∼ 0.01pc inferred for NGC 1566 (Alloin et al 1985;da Silva et al 2017). The rapidly variable narrow Fe Kα line have also been reported in the AGN NGC 4151 (Zoghbi et al 2019), which can be explained as originating from the inner BLR.…”
Section: Response Of the Fe Kα Emission To The Longterm X-ray Continu...supporting
confidence: 60%
“…For example, the multiplet 42 lines of FeII are clearly seen superimposed on the [OIII] lines in our spectrum, but these were not detected in NGC 1566's low state (see fig. 10 in da Silva et al 2017).…”
Section: Optical Spectrum: New Resultsmentioning
confidence: 99%
“…The lag of the K band variability relative to J was however elsewhere found to be less than 20 days (Oknyanskij & Horne 2001). Alloin et al (1985) and da Silva et al (2017) found the broad line region upper limit radius to be 20 light-days and 15 light-days respectively. These values together with the IR time delays may be used to estimate the location of the inner edge of the dust torus (see e.g., Clavel et al 2000;Netzer 2015).…”
Section: Introductionmentioning
confidence: 98%
“…These investigations of NGC 1566 have long history (see e.g. references at da Silva et al 2017; Oknyansky et al 2019b; Oknyansky et al 2020; Parker et al 2019). The NGC1566 is one of the brightest and nearest galaxies with active galactic nuclei (AGN) in the South Hemisphere.…”
Section: Introductionmentioning
confidence: 99%